Costs of TB care incurred by adult patients with newly diagnosed drug-sensitive TB in Ballabgarh block in northern India. (9th April 2021) - Chandra, Ankit; Kumar, Rakesh; Kant, Shashi; Krishnan, Anand
Abstract: Background: India's National Tuberculosis Elimination Programme (NTEP) provides free diagnosis and treatment services but does not monitor TB-related costs. This study aimed to estimate the direct and indirect costs borne by adult patients with newly diagnosed TB. Methods: A longitudinal study in Ballabgarh block, Haryana (North India) was conducted. A total of 110 patients were interviewed and data regarding costs were collected at three points of time (after diagnosis, at the end of intensive phase and at the end of the treatment) using a semistructured questionnaire. The total direct (out-of-pocket expenses) and indirect (income lost) costs before and during treatment were calculated for patients who completed the treatment. Results: We enrolled 110 patients with drug-sensitive TB; 6 patients could not complete the treatment. The TB-related median total cost was US$150 (IQR 65–335). The median prediagnosis and postdiagnosis costs were US$42 (IQR 19–313) and US$63 (IQR 10.2–190), respectively. The median direct and indirect costs were US$75 (IQR 36–148) and US$16 (IQR 0–197), respectively. A catastrophic cost was experienced by 18% (95% CI 12 to 27%) of households. Conclusion: Despite free diagnosis and treatment services, there is a substantial TB-related cost for TB care under the NTEP. Accelerated efforts are needed to achieve the target of zero catastrophic cost.